The plant-like structure of lance sea urchin spines as biomimetic concept generator for freeze-casted structural graded ceramics - Klang, Katharina; Nickel, Klaus G. (Biomimetics, 2021)
The spine of the lance sea urchin (Phyllacanthus imperialis) is an unusual plant-akin hierarchical lightweight construction with several gradation features: a basic core-shell structure is modified in terms of porosities, pore orientation and pore size, forming superstructures. Differing local strength and energy consumption features create a biomimetic potential for the construction of porous ceramics with predetermined breaking points and adaptable behavior in compression overload. We present a new detailed structural and failure analysis of those spines and demonstrate that it is possible to include at least a limited number of those features in an abstracted way in ceramics, manufactured by freeze-casting. This possibility is shown to come from a modified mold design and optimized suspensions.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Alumina; Biomimetic; Fracture behavior; Freeze-casting; Microcomputed tomography (Μct); Porous ceramic; Sea urchin spine; Structural graded material